The role of narcissistic leadership in the effect of internal marketing on creative employee performance - Çiçek, Berat; Akıllıbaş, Erman; Kaynak, İnan (My University, 2022)
This study investigates the effect of internal marketing practices on creative employee performance and the role of narcissistic leadership in this interaction. In this context, a survey study was conducted with hotel, restaurant, and cafe (Horeca) employees, where internal marketing practices were intensively applied. According to the analysis results, it is found that internal marketing practices positively affected creative employee performance, internal marketing practices hurt narcissistic leadership, and narcissistic leadership negatively affected creative employee performance. In addition, it was found that narcissistic leadership partially mediated internal marketing and creative employee performance.